Does Generation Y Really Care about Celebrity in Their Purchase? The role of Customer Attitude as A Mediator - Binti Saupi, Norzaini; Harun, Amran; Othman, Bestoon; Aso Ali, Raman; Anwer Ismael, Darbaz (International Journal of Psychosocial Rehabilitation, 2019)
Past literature mostly focusedonsfictional brandsd and celebrities to understand their relationship with purchase intention. However, there is a recent call for studies to lookat genuine brandss andcelebritiesy in the study of purchase behavior. Therefore, this study aims to investigate the influence of a genuine celebrity endorser on customers’ attitude toward a brand and their purchase intention. A total of 200 questionnaires were disseminated to GenerationYagedabove,e 166years old.  The findings of the current study confirmed that celebrity endorsement dimensions such as trustworthiness and expertise have a positive and significant influence on the attitude and purchase intention among Generation Y. In contrast, the attractivenessofycelebrity endorsementst has no significant impact on Generation Y attitude toward a brand and purchase intention. The result also indicates a positive relationship between attitude toward a brand and purchase intention. The findings also revealed that attitude toward a brand mediates the relationship between celebrity endorsement and purchase intention among Generation Y. The current study empirically signifies that celebrity plays an important role in shaping Generation Y attitude toward a brand and enhancing their purchase intention in the multi-cultural context of Malaysia. Notably, marketing managers should emphasize the benefit of engaging a celebrity as an endorser for aparticulartproduct witho their targeted customers.